Torque allocation strategy for four in-wheel-motor drive electric vehicle based on layered control. (November 2022) - Chen, Wuwei; Zhao, Linfeng; Hu, Jinfang; Tan, Dongkui; Sun, Xiaowen
The differential torque of four in-wheel-motor drive electric automotive will affect vehicle stability, and applications of the differential driven assisting steering (DDAS) will be limited consequentially. To solve this problem, stability analysis and control system design is essential, therefore a DDAS stability control system is designed based on the layered control of yaw moment. Correlation functions are used to reflect the shifts of vehicle characteristic state between stable and unstable states, and help to determine the control weight of each subsystem in the lower-layer controller. In the lower-layer controller, the strategy of direct steering-wheel torque control is used to build a DDAS controller. Under different vehicle moving states, differential driving torque and yaw moment vary with the change of the control weights; and according to the theory of quadratic programming, optimal allocation of four-wheel driving torques will be made according to the total driving torque. The effectiveness of the proposed control system is verified by numerical simulation and hardware-in-the-loop experiment. The results show that the proposed control method can improve vehicle stability and ensure driving safety.